Optimasi Online Marketing Menggunakan Dynamic e-Commerce pada CV Noor Mandiri Rotan - Putri Kurnia Handayani; Noor Latifah; Syafiul Muzid (Muria Jurnal Layanan Masyarakat, 2021)
Online Marketing is a marketing system that uses internet media as a vehicle for marketing products. One type of marketing through the internet is buying and selling marketing, known as e-commerce. Dynamic e-commerce technique is a technique used in e-commerce websites that utilizes business intelligence in managing consumer spending patterns. The type of website used by CV Noor Mandiri Rattan so far is the introduction of marketing type, where the website only contains a business profile and several product catalogs owned so that the CV Noor Mandiri Rattan can be said to lag behind technological updates or use internet marketing techniques that are lagging behind. Seeing this, the Muria Kudus University service team helped in optimizing online marketing that has been owned by CV Noor Mandiri Rotan using dynamic e-commerce so that it can serve sales transactions and expand market share and increase company revenue.